Gender Differences in Flourishing among Indonesian Students - Asfarina, Lilla Maturizka Ayu (Indonesian Journal of Counseling and Development, 2025)
This study investigates differences in flourishing levels between male and female Indonesian college students. Flourishing is defined as a state in which individuals experience life satisfaction, perceive ongoing personal development, and contribute positively to others. The research employs a comparative design to examine whether significant differences exist between these two groups. Data were collected using an adapted Flourishing Scale, which measures meaning in life, social connectedness, and competence. The scale demonstrated strong validity and reliability, with a Cronbach's alpha of 0.85. The sample comprised 234 students from Java, Sumatra, Borneo, and Celebes, selected through convenience sampling via an online survey. Data analysis used an Independent-Samples T-Test, which revealed a p-value below 0.05. These findings indicate significant differences in flourishing levels between male and female college students in Indonesia. Further analysis of each flourishing aspect also revealed significant gender differences. These findings have significant implications for higher education. Understanding gender differences in flourishing enables faculty to develop targeted educational and counseling programs that support student well-being and academic achievement